Adoção inicial das normas contábeis internacionais por empresas brasileiras - Oliveira, Valdiney Alves de (2010)
This study aimed to identify at what level the accounting information both in the Brazilian and U.S. markets respond to the requirements of the initial adoption of IFRS - International Financial Reporting Standards. The global movement towards the convergence of International Accounting Standards ruled by the International Accounting Standards Board (IASB) resulted in the requirement for adoption of IFRS (mentioned above) for publicly traded Brazilian companies by the Securities Commission (known as CVM in Brazil) on CVM Instruction 457/07. A Descriptive Research was carried out as far as using statistics about the method of procedures, techniques of documentary research and classical content analysis. Financial statements prepared for the year of 2008 were analyzed in accordance both with U.S. GAAP and GAAP of 20 Brazilian companies from 10 economic sectors listed at the same time on the Stock Exchange of New York (NYSE) and the Stock Exchange (BOVESPA). The index of disclosure was calculated such as it was proposed on Lopes and Rodrigues study carried out a couple of years ago (2007) for Portuguese companies. The results point to indexes calculated for the disclosure of Form 20F higher than those calculated for the Standard Financial Statements (DFP), confirming a greater degree of convergence between U.S. GAAP and IFRS. It suggests that depending on the adoption of IFRS the consolidated accounting in GAAP tend to change substantially, increasing that way, the level of disclosure. Furthermore the results confirmed both by the sample and literature, that the sector of activity and size of enterprises directly influence the disclosure of information. In relation to the auditors the fact that the statements be audited by global audit companies known as the Big Four has not determined the extent of the disclosure.